2014
DOI: 10.1590/abd1806-4841.20142923
|View full text |Cite
|
Sign up to set email alerts
|

Exuberant clinical picture of Buschke-Fischer-Brauer palmoplantar keratoderma in bedridden patient

Abstract: Buschke-Fisher-Brauer keratoderma is a rare hereditary autosomal dominant disease of incomplete penetrance. Important differential diagnoses include other palmoplantar keratinization disorders, acquired or hereditary, which is done based on the histopathological findings. This diagnosis alerts especially about the possibility of associated neoplasms. Treatment involves topical keratolytic agents, usually with little efficacy, or with long-term systemic retinoids with follow-up of exuberant collateral effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although the etiology remains poorly understood, the loci located at 8q24.13-8q24.21 and 15q22-15q24 have been associated with PPK. Thorough analysis has shown that the collagen type XIV alpha 1 chain (COL14A1) and alpha and gamma adaptin binding protein p34 (AAGAB) genes, located in these loci, respectively, present pathogenic mutations in patients diagnosed with PPK and their family members (3). The AAGAB gene codes a 315 amino-acid protein that allows interaction between the gamma-adaptin and alpha-adaptin subunits to stabilize the AP2 adaptor during clathrin-mediated endocytosis (CME) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology remains poorly understood, the loci located at 8q24.13-8q24.21 and 15q22-15q24 have been associated with PPK. Thorough analysis has shown that the collagen type XIV alpha 1 chain (COL14A1) and alpha and gamma adaptin binding protein p34 (AAGAB) genes, located in these loci, respectively, present pathogenic mutations in patients diagnosed with PPK and their family members (3). The AAGAB gene codes a 315 amino-acid protein that allows interaction between the gamma-adaptin and alpha-adaptin subunits to stabilize the AP2 adaptor during clathrin-mediated endocytosis (CME) (4).…”
Section: Introductionmentioning
confidence: 99%